2023
DOI: 10.3390/molecules28020657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Time and Bacterial Strain on the Quality of Probiotic Goat’s Milk Using Different Types and Doses of Collagens

Abstract: Recently, increasing attention has been focused on developing new products based on goat’s milk. Consumers positively perceive fermented goat’s milk products as health-promoting due to their nutritional value, digestibility, and potential source of probiotics. This study aimed to evaluate the possibility of using different doses of collagen and collagen hydrolysate in the production of probiotic goat’s milk fermented by four monocultures: Lacticaseibacillus casei 431® Lactobacillus acidophilus LA- 5®, Lacticas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The analysis of the number of live bacterial cells before digestion indicated that ovine fermented milk showed more viable cells by 0.2–1.9 log cfu g −1 than caprine milk, considering similar fermentation conditions. Numerous studies confirmed that ovine milk contains higher dry matter, total protein, crude fat, casein, minerals, and vitamins compared to caprine milk [ 39 , 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of the number of live bacterial cells before digestion indicated that ovine fermented milk showed more viable cells by 0.2–1.9 log cfu g −1 than caprine milk, considering similar fermentation conditions. Numerous studies confirmed that ovine milk contains higher dry matter, total protein, crude fat, casein, minerals, and vitamins compared to caprine milk [ 39 , 40 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Raw ovine and caprine milk were heated at 85 °C for 30 min [ 47 , 48 , 49 ]. The cooled milk was divided into a total of 40 batches (20 batches for sheep’s milk and 20 batches for goat’s milk) based on the added probiotic strains ( L. casei , L. acidophilus , L. paracasei , and L. rhamnosus ) and different forms of collagen (bovine and protein hydrolysate) and doses (1.5% and 3.0%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations